Synergistic Antimicrobial Effects of Ibuprofen Combined with Standard-of-Care Antibiotics against Cystic Fibrosis Pathogens - Qingquan Chen; Marleini Ilanga; Sabona B. Simbassa; Bhagath Chirra; Kush N. Shah; Carolyn L. Cannon (Biomedicines, 2023)
Cystic fibrosis (CF) is a common life-shortening genetic disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. Lungs of CF patients are often colonized or infected with microorganisms requiring frequent courses of antibiotics. Antibiotic-resistant bacterial infections have been a growing concern in CF patients. Chronic bacterial infections and concomitant airway inflammation damage the lungs, ultimately leading to respiratory failure. Several clinical trials have demonstrated that high-dose ibuprofen reduces the rate of pulmonary function decline in CF patients. This beneficial effect has been attributed to the anti-inflammatory properties of ibuprofen. Previously, we have confirmed that high-dose ibuprofen demonstrates antimicrobial activity against P. aeruginosa both in vitro and in vivo. However, no study has examined the antimicrobial effect of combining ibuprofen with standard-of-care antimicrobials. Here, we evaluated the possible synergistic activity of combinations of common nonsteroidal anti-inflammatory drugs (NSAIDs), namely, ibuprofen, naproxen, and aspirin, with commonly used antibiotics for CF patients. The drug combinations were screened against different CF clinical isolates. Antibiotics that demonstrated increased efficacy in the presence of ibuprofen were further tested for potential synergistic effects between these NSAIDS and antimicrobials. Finally, a survival analysis of a P. aeruginosa murine infection model was used to demonstrate the efficacy of the most potent combination identified in in vitro screening. Our results suggest that combinations of ibuprofen with commonly used antibiotics demonstrate synergistic antimicrobial activity against drug-resistant, clinical bacterial strains in vitro. The efficacy of the combination of ceftazidime and ibuprofen against resistant P. aeruginosa was demonstrated in an in vivo pneumonia model.